Role of slip velocity in a magneto-micropolar fluid flow from a radiative surface with variable permeability: a numerical study - Sharma, Bhupendra Kumar; Tailor, Vikas; Goyal, Mahesh Chandra (Zielona Góra: Uniwersytet Zielonogórski)
An analysis is presented to describe the hydromagnetic mixed convection flow of an electrically conducting micropolar fluid past a vertical plate through a porous medium with radiation and slip flow regime. A uniform magnetic field has been considered in the study which absorbs the micropolar fluid with a varying suction velocity and acts perpendicular to the porous surface of the above plate.
Keywords: slip velocity; chemical reaction; micropolar fluid; MHD; heat transfer; mass transfer; FDM (Fused Deposition Modeling)